2019
DOI: 10.1111/jcmm.14870
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol reduces oxidative stress and activates Nrf2/p62 to attenuate diabetic cardiomyopathy in rats

Abstract: Allopurinol (ALP) attenuates oxidative stress and diabetic cardiomyopathy (DCM), but the mechanism is unclear. Activation of nuclear factor erythroid 2-related factor 2 (Nrf2) following the disassociation with its repressor Keap1 under oxidative stress can maintain inner redox homeostasis and attenuate DCM with concomitant attenuation of autophagy. We postulated that ALP treatment may activate Nrf2 to mitigate autophagy over-activation and consequently attenuate DCM. Streptozotocin-induced type 1 diabetic rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 51 publications
(160 reference statements)
3
68
0
Order By: Relevance
“…Previous studies have suggested that oxidative stress is the primary pathological response to hyperglycemia treatment in cells ( Luo et al, 2020 ; Zhou and Toan, 2020 ). Thus, we subjected cardiomyocytes to hyperglycemia with or without matrine pretreatment, and used immunofluorescence to measure intracellular and mitochondrial ROS levels.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that oxidative stress is the primary pathological response to hyperglycemia treatment in cells ( Luo et al, 2020 ; Zhou and Toan, 2020 ). Thus, we subjected cardiomyocytes to hyperglycemia with or without matrine pretreatment, and used immunofluorescence to measure intracellular and mitochondrial ROS levels.…”
Section: Resultsmentioning
confidence: 99%
“…Both GO and rGO exhibited cardiotoxicity by mediating lipid peroxidation, oxidative stress, and mitochondrial dysfunction. Previous reports revealed that β-estradiol or allopurinol treatment can be used for protection of cell and tissue damages against oxidative stress in H9c2 cells and cardiac tissues through upregulating heme oxygenase expression ( Barta et al, 2018 ; Chen et al, 2019 ; Luo et al, 2020 ). It will be interesting to test whether related pharmacological interventions could alleviate the cytotoxicity of graphene family nanomaterials in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Superoxide production by dihydroethidium (DHE) staining method as previously described (Luo et al, 2019). Briefly, the CMs were in six‐well plates at a density of 1 × 10 5 cells/plate.…”
Section: Methodsmentioning
confidence: 99%
“…The cell supernatants were collected, and the levels of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-1β (IL-1β) levels were measured by enzyme-linked immunosorbent assay (ELI-SA) kits according to the manufacturer's introductions (Kang et al, 2020). Superoxide production by dihydroethidium (DHE) staining method as previously described (Luo et al, 2019). Briefly, the CMs were in sixwell plates at a density of 1 × 10 5 cells/plate.…”
Section: Measurement Of Inflammation Factorsmentioning
confidence: 99%